Megaripple Migration on Mars. Issue 8 (29th July 2020) - Silvestro, S.; Chojnacki, M.; Vaz, D. A.; Cardinale, M.; Yizhaq, H.; Esposito, F.
Abstract: Aeolian megaripples, with 5‐ to 50‐m spacing, are abundant on the surface of Mars. These features were repeatedly targeted by high‐resolution orbital images, but they have never been observed to move. Thus, aeolian megaripples (especially the bright‐toned ones often referred as Transverse Aeolian Ridges—TARs) have been interpreted as relict features of a past climate. In this report, we show evidence for the migration of bright‐toned megaripples spaced 1 to 35 m (5 m on average) in two equatorial areas on Mars indicating that megaripples and small TARs can be active today. The moving megaripples display sand fluxes that are 2 orders of magnitudes lower than the surrounding dunes on average and, unlike similar bedforms on Earth, can migrate obliquely and longitudinally. In addition, the active megaripples in the two study areas of Syrtis Major and Mawrth Vallis show very similar flux distributions, echoing the similarities between dune crest fluxes in the two study areas and suggesting the existence of a relationship between dune and megaripple fluxes that can be explored elsewhere. Active megaripples, together with high‐sand flux dunes, represent a key indicator of strong winds at the surface of Mars. A past climate with a denser atmosphere is not necessary to explain their accumulation and migration. Plain Language Summary: Similar to what is found in deserts on Earth, the wind has accumulated sandy landforms (bedforms) on the Martian surface, such as dunes and ripples. Ripples on Earth are mostly spaced at 10 cm, but a particular kind of ripples called "megaripples" can be 30 cm to tens of meters spaced. Megaripples have coarse sand grains (>1 mm) accumulated at their crests, so only strong winds can move them. Mars has a faint atmosphere, and according to computer models, winds able to mobilize coarse sand grains are not predicted to blow at the surface. Thus, Martian megaripples are often considered to be static relics of a past climate where the atmosphere was denser. Here we show the first evidence for the movement of bright megaripples on Mars showing that some of these bedforms can be active today and do not require past climatic states for their origin as has been assumed. Key Points: Bright‐toned megaripple migration is identified on the surface of Mars for the first time These features are similar to Transverse Aeolian Ridges, which had been assumed to be dormant under the current climate Megaripple crest fluxes are, on average, 2 orders of magnitude lower than local dune crest fluxes